A novel digital technique for maintaining maxillomandibular relations in fixed prosthetic rehabilitations. (November 2021) - Li, Junying; Galli, Matthew; Chen, Zhaozhao; Venezia, Pietro; Mangano, Francesco; Lepidi, Luca
Abstract: Introduction: In fixed prosthetic rehabilitations, the restorations must be designed and fabricated in a proper maxillomandibular relationship, with correct vertical dimensions of occlusion (VDO) and centric relation (CR). This short communication introduces a novel digital technique that allows to obtain the maxillomandibular record and transfer it throughout the treatment procedure. Methods: The protocol consisted of the following steps: 1. scan-jig planning and production; 2. maxillomandibular record prior to tooth preparation; 3. sequential tooth preparation and post-operative data recording through a cut-out and re-scan protocol; 4. control of the pre- and post-operative alignment of the scans in the correct VDO and CR, design and delivery of the definitive restorations. Results: There was no clinical difference in the spatial positions of the virtual models and the relationships between the arches throughout every step of the treatment. Conclusion: The main advantages of this technique are that it allows to maintain the therapeutic maxillomandibular relationship after its clinical evaluation, to reduce chair time and to avoid inaccuracies determined by multiple bite registrations.